THE VIEWS AND EXPERIENCES OF LGBTQ+ PEOPLE REGARDING MIDWIFERY CARE: A SYSTEMATIC REVIEW OF THE INTERNATIONAL EVIDENCE - Mc Cann, Edward (My University, 2021)
Background There has been growing attention to addressing the health inequalities and concerns of LGBTQ+ people, with research evidence highlighting areas requiring further attention and development. The distinct concerns of LGBTQ+ people when accessing midwifery care and support is an issue requiring a specific focus to ensure needs are met effectively. Aim The aim of this systematic review was to critically appraise and synthesise the best available evidence regarding the views and experiences of LGBTQ+ people in relation to midwifery care and supports. Method A systematic review was undertaken to identify all relevant studies meeting the inclusion criteria. A total of eleven papers were included in the review, utilising the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) method. Methodological quality was evaluated using the Mixed Methods Assessment Tool (MMAT). Findings Following data analysis, the themes that emerged were: (i) Contemplating pregnancy and ante-natal experiences, (ii) pregnancy and labour issues and concerns, and (iii) post-natal ongoing care and supports. Conclusion and implications for practice It has become apparent from this systematic review that LGBTQ+ individuals have variable experiences when accessing midwifery care and support. Midwifery policies and practice guidelines should be reflective of the distinct needs of LGBTQ+ people and their families and friends. Future studies could focus more on the impact and outcomes of their care experiences within midwifery services.
PUBLISHED
Keywords: Midwifery; Nurse midwife; LGBTQ; Care and support; Education; Inclusive Society; LGBT; LGBTI; LGBTQ+; MIDWIFERY EDUCATION; Midwifery Care; SYSTEMATIC REVIEW